The Impact of Government Revenue and Current Expenditure Polices’ Implementation on the Inflation Rate of Lao PDR by Using Vector Autoregression (VAR) - PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of this research is 1) to investigate the impact of revenue and expenditure policies’ implementation of the government on inflation in Lao PDR by using Vector Autoregression (VAR) model, and 2) to analyze the adjustment of the inflation rate using impulse response function (IRF) and variance decomposition analysis (VDA). The researcher used the quarterly data from the database of the Bank of Lao PDR and Ministry of Finance in the period of 2010-2020, and analyzed the data with the EViews 9 program which data was adjusted to be stationary with Optimal Lag length Selection, then estimate the equation on basis of VAR model with the Ordinary least squares method of least squares. The results revealed that: 1) impact of revenue and expenditure policies’ implementation of the government on inflation in Lao PDR by using VAR model indicated that all the variables are lag 1 yielded, which changing the government expenditure in the last quarter has same direction impact the change in the inflation rate of the Lao PDR, and the change in the government income in the last quarter has opposite direction the change in the inflation rate of the Lao PDR. 2)The adjustment of the inflation rate was analyzed using impulse response function (IRF) found that the change in shock of inflation rate, current expenditure, and the government’s revenue have effected from 2nd quarterly to the 12th quarterly, which Inflation rate and government revenue have the most impact and government’s current expenditure has the least impact. As for the results of variance decomposition analysis (VDA) found that inflation rate can explain variance at a high level from the 1st quarter and gradually decreases until the 12th quarter, which government’s revenue and current expenditure can explain variance increasing continuously from 2nd quarterly to the 12th quarterly. The research concluded that last quarter’s government revenue had a negative effect on the current quarter’s inflation rate, and last quarter’s government current expenses had a positive effect on the inflation rate.